The involvement of GABA-rho receptors in regulating ethanol-induced elevation of dopamine, glycine and taurine within the nucleus accumbens of Wistar rats - Cadeddu, Davide; Loftén, Anna; Ademar, Karin; Söderpalm, Bo; Adermark, Louise; Ericson, Mia (Frontiers in Pharmacology, 2025)
IntroductionAlcohol use disorder (AUD) causes significant morbidity and mortality globally. Ethanol’s rewarding and reinforcing effects are attributed to activation of the mesolimbic dopamine system, increasing accumbal dopamine release. While activation of accumbal glycine receptors (GlyRs) is a prerequisite for ethanol-induced dopamine signaling, multiple transmitter systems may be involved; recent research implicates the GABA-rho receptor as a prominent target. Considering the structural and functional similarities between GlyRs and GABA-rho receptors, this study aimed to define the role of GlyRs and GABA-rho receptors in regulating baseline dopamine signalling and ethanol-induced elevation of extracellular dopamine and GlyR agonists, as well as to determine their involvement in the action of the ethanol relapse-preventing drug acamprosate.MethodsTo investigate this, in vivo microdialysis was conducted in male Wistar rats.Results and discussionLocal perfusion with either the GABA-rho receptor antagonist TPMPA or the GlyR antagonist strychnine prior to ethanol administration significantly reduced the ethanol-induced increase in dopamine levels. These findings suggest that both GlyRs and GABA-rho receptors are involved in mediating the dopamine-elevating effect of ethanol. In addition, a significant attenuation of the ethanol-induced glycine and taurine elevation was observed following both pretreatment with TPMPA and strychnine, whilst only GlyR blockade inhibited the acamprosate-induced increase of dopamine. Unlike strychnine, TPMPA alone did not alter dopamine levels, suggesting that GABA-rho receptors display features that distinguish them from GlyR. In conclusion, GABA-rho receptors regulate ethanol-induced dopamine and glycine/taurine levels within the nAc without affecting basal dopamine neurotransmission, suggesting their potential as a pharmacological target for the treatment of AUD.